Retrospective analysis of the clinical significance of Ro52/TRIM21 antibody and specific antinuclear antibody patterns by indirect immunofluorescence - Kaifang Liu,; Yunfeng Liao,; Pu Li,; Jing Shi, (Journal of the Pakistan Medical Association, 2024)
Objectives: To determine the clinical significance of Ro52 protein/tripartite motif-containing 21 antibody and specific antinuclear antibody patterns using indirect immunofluorescence technique. Method: The retrospective study was conducted at the clinical laboratory of the First Affiliated Hospital of Chongqing Medical University, China, and comprised data from January 2017 to December 2021 of patients who underwent antinuclear antibody and anti-extractable nuclear antigen antibody detection. Inpatients with Ro52 antibody-positive status were taken as the cases, while anti-Ro52 negative patients with clear clinical diagnosis were taken as the controls. Data was analysed using SPSS 19. Results: There were 1802 cases and 1211 controls. Positive Ro52 showed significantly greater frequency in patients with primary Sjogren’s syndrome, systemic lupus erythematosus, inflammatory myositis, dry eyes and interstitial lung disease (p<0.05). Ro52 antibody showed high positive predictive value for primary Sjogren’s syndrome 25(96.15%), systemic lupus erythematosus 259(91.20%), connective tissue disease-associated interstitial lung disease 45(86.67%) and inflammatory myositis 60(86.67%). Antinuclear antibody indirect immunofluorescence patterns most frequently detected were nuclear speckled 128(40.89%) and cytoplasmic speckled 126(40.26%) (p<0.05). Interstitial lung disease was associated with the presence of cytoplasmic speckled antinuclear antibody indirect immunofluorescence pattern 24(19.2%), while tumours 47(36.5%) and hepatitis B 26(20.3%) seemed to be more frequent with nuclear speckled pattern (p<0.05). The simultaneous reactivity extractable nuclear antigen antibodies most frequently detected were antinuclear antibody+Ro52+anti-Sjogren's syndrome A+ 558(33.96%). Conclusion: Ro52 antibody positivity was found to be associated with Sjogren’s syndrome, systemic lupus erythematosus, inflammatory myositis, dry eye and interstitial lung disease. The antinuclear antibody immunofluorescence pattern of Ro52 positive was single and primarily granular cytoplasm type. Antinuclear antibody negative and Ro52 positive in the serum of patients also had certain significance in auxiliary disease diagnosis. Key Words: Anti-Ro52 autoantibody, Autoimmune disease, Sjogren's syndrome, Xerophthalmia, Tripartite motif-containing 21 protein.